2018
DOI: 10.1016/j.solmat.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor organic photovoltaic module characteristics: Benchmarking against other PV technologies for performance, calculation of Ross coefficient and outdoor stability monitoring

Abstract: A comparison of performance parameters for first, second and third generation PV technologies has been conducted. Organic photovoltaic (OPV) modules displayed markedly different outdoor performance characteristics to other PV technologies owing to the positive temperature coefficient, lower thermal mass and response under low light conditions. The linear relationship between irradiance and module temperature rise above ambient is studied, leading to calculation of values for the Ross coefficient for OPV module… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 36 publications
2
41
0
Order By: Relevance
“…At the higher irradiance level, the modules demonstrate a small drop in VOC, which is overwhelmed by increases in JSC and FF leading to a slight positive PCE coefficient (+0.0078 %/K). This is particularly interested as very few PV technologies possess a positive temperature coefficient in outdoor conditions (OPVs and DSCs are the exceptions) [9] which supports the indoor data supplied by Leong et al [28].…”
Section: Diurnal Performancesupporting
confidence: 73%
See 2 more Smart Citations
“…At the higher irradiance level, the modules demonstrate a small drop in VOC, which is overwhelmed by increases in JSC and FF leading to a slight positive PCE coefficient (+0.0078 %/K). This is particularly interested as very few PV technologies possess a positive temperature coefficient in outdoor conditions (OPVs and DSCs are the exceptions) [9] which supports the indoor data supplied by Leong et al [28].…”
Section: Diurnal Performancesupporting
confidence: 73%
“…Visoly-Fisher et al showed OPV devices can rise in temperature with exposure to sunlight even with the IR part of the spectrum omitted [30]. The figures for Ross coefficient are slightly lower than those obtained in previous experiments by this group on organic photovoltaic (OPV) modules (0.027 K m 2 /W) and polycrystalline (poly-Si) modules (0.028 K m 2 /W) [9]. The difference is partly due to the location of the PT100 temperature sensor which was positioned behind the glass substrate that the modules were laminated onto, and partly due to the large substrate to active area ratio; both these factors leading to temperature loss and a reduction in the Ross coefficient.…”
Section: Effect Of Temperature On Psc Performancementioning
confidence: 70%
See 1 more Smart Citation
“…Despite the great achievements in improving efficiency, commercialization of large-scale OSCs is limited due to their relatively low environmental stability 8,[12][13][14][15][16] . Of note is that many environmental issues (e.g., heat, oxygen, light, and humidity) have been identified as main factors of device degradation 17 . These parameters should be properly addressed to meet the requirements of practical outdoor application of OSCs.…”
mentioning
confidence: 99%
“…The simulation results are shown in Section III. The PV modules performance in terms of voltage, current and power have been monitored in an outdoor environment [11] and they will be compared with model obtained in MATLAB/Simulink in Section IV.…”
Section: Introductionmentioning
confidence: 99%